2018
DOI: 10.1001/jamainternmed.2017.5038
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Pesticide Residue Intake From Consumption of Fruits and Vegetables and Pregnancy Outcomes Among Women Undergoing Infertility Treatment With Assisted Reproductive Technology

Abstract: for the EARTH Study Team IMPORTANCE Animal experiments suggest that ingestion of pesticide mixtures at environmentally relevant concentrations decreases the number of live-born offspring. Whether the same is true in humans is unknown.OBJECTIVE To examine the association of preconception intake of pesticide residues in fruits and vegetables (FVs) with outcomes of infertility treatment with assisted reproductive technologies (ART). DESIGN, SETTING, AND PARTICIPANTSThis analysis included 325 women who completed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
73
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 102 publications
(83 citation statements)
references
References 52 publications
5
73
0
1
Order By: Relevance
“…Findings from two cross-sectional reports on semen parameters detailed mixed findings, and although the majority of tested parameters showed no significant differences, higher sperm concentration in O consumers [50] and lower normal sperm in NO consumers [51] offer preliminary data that is worthy of further exploration. In female fertility, very positive associations between low dietary pesticide exposure and successful pregnancy and birth outcomes in women undergoing assisted reproduction have been reported in one study [52]. Given the declining fertility rates and poorer semen quality being reported worldwide [74], higher odds of achieving clinical pregnancy and live birth with an organic diet is a significant and important finding.…”
Section: Observational Researchmentioning
confidence: 95%
See 2 more Smart Citations
“…Findings from two cross-sectional reports on semen parameters detailed mixed findings, and although the majority of tested parameters showed no significant differences, higher sperm concentration in O consumers [50] and lower normal sperm in NO consumers [51] offer preliminary data that is worthy of further exploration. In female fertility, very positive associations between low dietary pesticide exposure and successful pregnancy and birth outcomes in women undergoing assisted reproduction have been reported in one study [52]. Given the declining fertility rates and poorer semen quality being reported worldwide [74], higher odds of achieving clinical pregnancy and live birth with an organic diet is a significant and important finding.…”
Section: Observational Researchmentioning
confidence: 95%
“…From a total of 20 publications including 13 cohorts, seven prospective cohorts were identified, with the majority involving mother/child pairs. These included the Norwegian Mother and Child Cohort Study [55,56]; KOALA Birth Cohort [58][59][60]; ALLADIN study [61]; PELAIGE Mother-Child Cohort [62] and the EARTH study [52]. Two adult-only cohorts involved development of cancer incidence in the Million Women Study [65], and self-reported health factors in the Nutri-Net Santé Cohort Study [20,53,63,64].…”
Section: Observational Cohort Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in both human and nonhuman studies, intake of soy food and folates was found to be protective against the adverse reproductive effects of bisphenol-A (166)(167)(168)(169). A recent study has shown that the presence of high pesticide residues in fruits and vegetables might modify the beneficial effects of fruits and vegetables on reproductive success (170). Because environmental contaminants are widely dispersed, future studies may need to consider coexposure to environmental contaminants (and mixtures of these contaminants) when investigating the associations between food/nutrients and health outcomes to better form dietary recommendations and guide action for general and susceptible populations.…”
Section: Emerging Concernsmentioning
confidence: 99%
“…The feasibility of applying this improved dietary insecticide exposure-assessment questionnaire to epidemiological research was then demonstrated by its application to a study of men and women undergoing treatment at a reproductive technology clinic. Significant associations were reported between higher (top quartile versus bottom quartile) intake of high-insecticide residue fruits and vegetables and lower (18% 95% CI: 5%-30%) incidence of pregnancy (421).…”
Section: Unanswered Questions and Future Researchmentioning
confidence: 96%